2018
DOI: 10.1002/hep4.1257
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin 1 Acts As a Negative Regulator of Wingless/Integrated‐Beta‐Catenin Signaling in Murine Liver and Human Liver Cancer Cells

Abstract: Prohibitin1 (PHB1) is a mitochondrial chaperone with diverse functions that include cell proliferation, apoptosis, and mitochondrial homoeostasis. Liver‐specific Phb1 knockout (KO) mice develop spontaneous injury and hepatocellular carcinoma (HCC). Our previous work demonstrated that PHB1 negatively regulates the H19‐insulin‐like growth factor 2 (IGF2)‐H19‐IGF2 axis signaling pathway and E‐box activity in hepatocytes and HCC cells. Phb1 KO livers exhibited increased expression of multiple wingless/integrated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…Accordingly inhibitors of PI3K signaling have been suggested as potential therapeutic agents in NSCLC . Some studies have found that PI3K‐AKT‐mTOR may negatively regulate the classic WNT signaling pathway through the downstream effector GSK3β . The relationship between circ‐IGF1R and key factors such as GSK3β may also be worth exploring in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly inhibitors of PI3K signaling have been suggested as potential therapeutic agents in NSCLC . Some studies have found that PI3K‐AKT‐mTOR may negatively regulate the classic WNT signaling pathway through the downstream effector GSK3β . The relationship between circ‐IGF1R and key factors such as GSK3β may also be worth exploring in the future.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Some studies have found that PI3K-AKT-mTOR may negatively regulate the classic WNT signaling pathway through the downstream effector GSK3β. 48,49 The relationship between circ-IGF1R and key factors such as GSK3β may also be worth exploring in the future. It was revealed that circ-IGF1R not only affects HCC through PI3K-AKT-mTOR, but also may promote the growth and metastasis of lung cancer through PI3K-AKT-mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…7 PHB1 also acts as a negative regulator of the Wingless-related integration site (WNT)/β-catenin signaling in the liver, in part through E2F1. 8 Finally, we recently showed that reduced PHB1 expression induced interleukin-8 ( IL-8 ) transcription by activating nuclear factor-kappa B (NF-κB) and activator protein 1 (AP-1), which resulted in enhanced IL-8 expression and release to promote tumorigenesis. 9 PHB1 was unable to bind to the IL-8 promoter by itself but it was able to bind in the presence of c-JUN, a finding that suggests the possibility of PHB1 acting as a co-repressor of the AP-1 site.…”
Section: Nuclear Phb1mentioning
confidence: 99%
“…1 In the liver, PHB1 acts mainly as a tumor suppressor and its deficiency results in liver injury and cancer. 49 This review examines the role of PHB1 in liver pathology focusing on the how its subcellular localizations, PTMs, and interactome may regulate its different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced PHB1 expression has also been shown to induce IL-8 transcription by activating NF-κB and AP-1, resulting in enhanced IL-8 expression and release to promote tumorigenesis[99]. Finally, PHB1 also acts as a negative regulator of WNT signaling, and its downregulation causes the induction of multiple WNT ligands and downstream activation of canonical WNT ‐β‐-catenin signaling in murine liver and human HCC cells, in part through E2F[100].…”
Section: Consequences Of Mat Genes Dysregulation In the Development Omentioning
confidence: 99%